PCR-RFLP assays to distinguish the Western and Eastern phylogroups in wild and cultured tench Tinca tinca - Lajbner, Z; Kotlík, P (Molecular ecology resources, 2011)
The tench Tinca tinca is a valued table fish native to Europe and Asia, but which is now widely distributed in many temperate freshwater regions of the world as the result of human-mediated translocations. Fish are currently being transplanted between watersheds without concern for genetic similarity to wild populations or local adaptation, and efficient phylogeographic markers are therefore urgently needed to rapidly distinguish genetically distinct geographical populations and to assess their contribution to the hatchery breeds and to the stocked wild populations. Here, we present a new method to distinguish recently discovered and morphologically undistinguishable Western and Eastern phylogroups of the tench. The method relies on PCR-RFLP assays of two independent nuclear-encoded exon-primed intron-crossing (EPIC) markers and of one mitochondrial DNA (mDNA) marker and allows the rapid identification of the Western and Eastern phylogroup and also of three geographical mtDNA clades within the Eastern phylogroup. Our method will enable researchers and fishery practitioners to rapidly distinguish genetically divergent geographical populations of the tench and will be useful for monitoring the introduction and human-mediated spread of the phylogroups in wild populations, for characterization of cultured strains and in breeding experiments.
Keywords: Cyprinidae; Phylogeny; mitochondriální DNA; DNA, Mitochondrial; Asia; polymorfismus délky restrikčních fragmentů; Evropa; Fish Proteins; Europe; Polymerase Chain Reaction; rybí proteiny; polymerázová řetězová reakce; Animals; Polymorphism, Restriction Fragment Length; Asie; zvířata; fylogeneze